Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Dan Model Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) Terhadap Hasil Belajar Matematika Siswa Pada Materi Garis Singgung Lingkaran - Nurina Kurniasari Rahmawati; Iip Ripati Hanipah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
This research is to prove whether the learning result of Student Mathematics with cooperative learning model of TPS type is better than the result of student learning of Mathematics with STAD type cooperative learning model on tangent material of circle. The population is the students of State Junior High School 1 East Cikarang. The sample was taken by using cluster random sampling technique from the population by randomized method, ie students of class VIII F and class VIII G as many as 60 students. The analysis test is done by normality test and homogeneity test. Normality test using Lilliefors test and Homogeneity test using Fisher test. While the hypothesis test using t-test. Based on the calculation obtained data that Lilliefors model of cooperative learning model type TPS Lhitung = 0.0954 and for Ltabel = 0.161 (0.0954 < 0.161) and for cooperative learning model type STAD = 0.1266 and for Ltabel = 0.161 (0, 1266 < 0.161), so it can be concluded that the cooperative learning model of TPS type and STAD type cooperative learning model come from the normally distributed population. Homogeneity test using Fisher test obtained Fhitung = 1.15 and Ftabel = 1.86 (1.15 < 1.86) so that TPS and STAD homogen. Hypothesis testing obtained thitung = 2.388 and ttable = 1.651. Because thitung > ttable then H0 is rejected. The conclusion of this research is there are difference of mathematics learning result of students using cooperative learning model of TPS type and mathematics learning result of students using STAD type cooperative learning model in tangent circle material in class VIII SMPN 1 Cikarang East Bekasi.